The Contribution of Oil Palm Partnerships to Increased Income of Plasma Farmers: A Study at PT. Windu Nabatindo Lestari (WNL) - Kurniawan, Indra; Elfatma, Olivia; Saloko, Subakho Aryo; Setyawan, Heri (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2021)
The income level of smallholder farmers can only meet their daily needs due to the location's remote location and the difficulty of communication access. Based on this, the Government seeks to formulate policies that are expected to have a real impact on increasing the productivity of smallholdings and improving the welfare of farmers. One of the efforts made is the Primary Member Cooperative Credit (KKPA). The purpose of this research is to examine the impact of the partnership program at the Windu Nabatindo Lestari (WNL) company in the KKPA scheme, a program to improve the welfare of plasma farmers. The research method is descriptive analysis with a qualitative approach using purposive sampling. Research respondents were 60 plasma farmers. Data collection techniques include field observations, in-depth interviews with questionnaires, and analysis of company documents. The results showed an increase in the welfare of plasma farmers after the partnership program. The partnership program at the Windu Nabatindo Lestari (WNL) company under the KKPA scheme positively impacts the welfare of plasma farmers in Pundu Village, Cempaga Hulu District East Kotawaringin, Central Kalimantan. The frequency of the number of plasma farmers who experienced increased income before and after the KKPA program was 83.3%.